Identity: The Demand for Dignity and The Politics of Resentment - Tooba Ghaffar (CISS Insight Journal, 2022)
Francis Fukuyama is an eminent and well-regarded scholar in the American political and academic circles. His book, The End of History and the Last Man, which he wrote at the collapse of the Soviet Union in 1992, was a must read for students of international relations in the 1990s. The book convincingly argued that in the Hegelian dialectical sense, the synthesis or outcome of the twentieth century social and political struggles was not a ‘communist utopia’, as theorized by Karl Marx. Instead, ‘global capitalism’ or ‘liberalism and market economy’ emerged as the viable and preferred system for people to organize their economy and society. In the book under review, Fukuyama further dives into the themes he has taken interest in since 1992: thymos (the part of the soul that craves recognition), dignity, immigration, nationalism, religion and culture.